Multi-scale processes of the Kelvin-Helmholtz instability at Earth’s magnetopause - Rice, Rachel C.; Blasl, K. A.; Nykyri, Katariina; Kavosi, Shiva; Sorathia, Kareem A.; Liou, Yu-Lun (Frontiers in Astronomy and Space Sciences, 2024)
The Kelvin-Helmholtz Instability (KHI) is a large scale convective instability which occurs anywhere the velocity shear between two fluids is large, such as Earth’s magnetopause where the fast flowing magnetosheath abuts the relatively stagnant outer magnetosphere. The KHI was initially believed to contribute only to energy and momentum transfer from the solar wind to the magnetosphere, but was eventually shown to support mass transport and plasma heating. Recent advancements in in-situ observational capabilities and high scale computer modeling have once again shifted our understanding of the KHI from a large scale process, to an active environment which connects the global and kinetic scales through a variety of multi-scale processes and phenomena. In this mini-review, we provide an update on the latest findings in Kelvin-Helmholtz (KH) related processes at kinetic scales and the effects of the global environment on KH development.